Book Review of "Nuclear Deterrence in South Asia: New Technologies and Challenges to Sustainable Peace" - Salman Ali Bettani (International Journal of Nuclear Security, 2025)
Nuclear deterrence has been the most intriguing subject in the field of strategic studies with the specific orientation of various security complexes across the globe. The South Asian strategic context offers a diverse ground for deterrence discourse owing to certain geopolitical and geostrategic realities. The main actors on the fulcrum are India and Pakistan, affecting the balance with their ever-growing strategic weapons programs. In six chapters by eminent scholars and academicians (Rizwana Abbasi and Zafar Khan), Nuclear Deterrence in South Asia: New Technologies and Challenges to Sustainable Peace comprehensively encompasses these developments from the perspective of new technologies and their implications on the sustainability of peace in the region. The academic strength of the argument theoretically revolves around the debate of the security dilemma, strategic stability, deterrence stability, and defensive realism explaining both the geo-economic and geostrategic dynamics at global and regional levels. The most interesting scholarly significance developed by the authors is the interlinked politics between the Asia Pacific and South Asia.